Complexity of Dual Employment in Department of Health and university, South Africa - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Dual employment was inherited from the Transkei government, which ruled that all doctorswho worked in hospitals also had to work in the medical school of the rural University. Policies at thisuniversity are inadequate, and where they do exist their implementation is discriminatory in nature.Case history: Mr. BM joined the Department of Health as a medical officer and was subsequently appointedas an acting head of department in the Department. He had to work in the health care system as well as atthe university full-time (Joint establishment); he was working on his own in his department. He was paid asa medical officer by the health but received no remuneration from university. This was contrary to labor lawand University policy and once the council realized this, a resolution was taken granting him back payment.Unfortunately, it was not implemented.Mr. BM was working against the post of professor and acting head and carried out all the responsibilitiesof that post without being remunerated. Although he was paid at the occupational-specific dispensation(OSD) scale in 2009, it was not adjusted till his retirement in 2018; therefore it affected his pension as well.The case history, short payment in salary, and unfair labor practice in respect of his dual employment arediscussed in this manuscript.Conclusion: The DOH must take responsibility in his dual employment for this shortfall in salary, as it isthe source of major funding.